Venturing into India: Singapore-India business ties - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
The business strategy of transplanting business models in India is one way which companies can penetrate the economic potential of the country. It is about taking proven business models and finding strategies to bring them into India where there are opportunities to scale up dramatically and where there is an opportunity to tap into local capital and management and create value for shareholders.Yet, SMEs in Singapore are "under-invested" in India ...